(untitled) (Physical Education, Health and Social Sciences, 2025)
This paper explores the theme of identity reclamation in Derek Walcott’s play Dream on a Monkey Mountain, emphasizing its unique engagement with the psychological aftermath of colonialism in the Caribbean context. While identity remains a recurrent concern in Walcott’s oeuvre, this play distinguishes itself by not only articulating the crisis of identity experienced by colonized individuals but also proposing a pathway toward its recovery. Central to this process is the character of Makak, whose fractured sense of self symbolizes the broader existential disorientation inflicted by colonial rule. Drawing theoretical support from Frantz Fanon’s seminal work The Wretched of the Earth, particularly the concept of counter-violence as a catalyst for decolonial awakening, the study contends that Makak’s dream-induced journey reflects a symbolic resistance against colonial subjugation. The hallucinatory and supernatural elements within the play serve to authenticate the psychological realism of this transformation, enabling Walcott to craft a mythopoetic framework for Caribbean self-reclamation. Ultimately, the paper asserts that Walcott not only captures the lived trauma of colonized subjects but also envisions a radical reimagining of their identity, aligning his creative vision with Fanon’s thought and marking his work as an indispensable voice in postcolonial literature.